Examining climate shocks and currency resilience in a stateless economy: evidence from Somalia’s informal exchange market - Nor, Mohamed Ibrahim (Frontiers in Climate, 2025)
This study explores the integration of Somalia’s unregulated exchange rate market with regional and global financial systems and investigates how climate-induced shocks influence currency resilience in a fragile, post-conflict context. The research utilizes time series data from 1995 to 2017 and employs advanced econometric techniques including the Johansen cointegration test, vector error correction model (VECM), Granger causality tests, impulse response functions, and variance decomposition. The model incorporates climate shock indicators to assess short-and long-run dynamics in exchange rate behavior. The results reveal significant long-term cointegration between the Somali Shilling and major regional and global currencies, suggesting deep financial integration. Short-term fluctuations are largely driven by regional currency movements. Climate shocks intensify exchange rate volatility, especially through channels such as agriculture, remittances, and trade, indicating structural vulnerabilities within the unregulated exchange system. The findings highlight the vulnerability of Somalia’s unregulated exchange market to external climate shocks, underscoring the need for formal integration of this system into national monetary frameworks. Policy actions should focus on strengthening institutional oversight, promoting transparent exchange rate mechanisms, and incorporating climate resilience strategies into monetary planning. In particular, a phased regulatory approach that aligns informal currency markets with regional and global financial systems could help stabilize exchange rate volatility and improve the country’s macroeconomic resilience. This is one of the first empirical studies to analyze the intersection of climate shocks and unregulated exchange rate systems in a post-conflict setting. It offers a novel framework for understanding informal financial systems within global economic networks. The study expands the literature on climate-finance linkages, informal currency markets, and post-conflict monetary systems by demonstrating how unregulated exchange structures interact with both environmental shocks and formal global markets.